Related party transactions and audit risk - Abdul Rasheed P. C; Iqbal Thonse Hawaldar; Mallikarjunappa T (Cogent Business & Management, 2021)
Related Party Transactions (RPTs) are perceived as genuine transactions, which fulfill the economic needs of a company. However, the controlling shareholders may use RPTs as a tool for transferring the firm's resources for their private benefit. The dual effect of RPTs, i.e., transaction efficiency and conflict of interest between the controlling shareholders and minority shareholders, increase audit risk and as a result, increases the audit fee. The Companies Act, 2013, and Clause 49 of the SEBI listing agreement mandate arm's length principle of pricing of RPTs. However, there are situations in which the regulations are silent about the method of pricing, and this increases the risk of auditors for auditing RPTs. This study intends to examine the relationship between RPTs and audit risk in India, based on a sample of 1,182 firms covering a period from 31 March 2011 to 31 March 2018. Panel data methodology has been applied for empirical analysis and the results show that higher audit fee is an indication of resource transferring RPTs. The results prove that instead of reducing the complexity associated with RPTs, the new RPTs regulations increase audit fee as a result of the increases in audit risk.
Keywords: M48; 650; Related party transactions; audit risk; conflicts of interests; transaction efficiency; firm performance; Arm's length price; India